Empreendedorismo social : análise dos investimentos de impacto no Brasil - Porto, Grace Kethellen Linhares Santos (2020)
Faced with a scenario in which social problems intensify and start to gain relevance in Brazil not only in the business world, but also in the academic world, social entrepreneurship appears as an opportunity to combat them generating several benefits for society. For this research, social entrepreneurship is seen as an activity that aims not only to solve a social problem, but also to generate profit from the sale of products or the provision of services and the possibility of distributing its dividends to partners, shareholders and others stakeholders. These characteristics, therefore, give rise to the so-called Social Impact Business. In accordance with the above, the present research aimed to analyze the process of attracting impact investment by social entrepreneurs in the main areas of impact business in Brazil. As for the methodology, the study is classified as descriptive, with a mixed approach, being, at first, quantitative and, later, qualitative, whose research method adopted is the study of multiple cases. For the quantitative stage, a questionnaire was made available through the Google Forms tool for social entrepreneurs representing business that have already captured investment. For the qualitative stage, interviews were conducted with a semi-structured script, via e-mail, with six business representatives from the main areas of socio-environmental impact, according to the survey carried out by the 2nd Socio-Environmental Impact Business Map (2019). Document analysis was also used as a source of evidence. For data analysis, the content analysis technique was used for qualitative data and simple descriptive statistics for quantitative ones. In summary, the results of the research showed that the impact businesses arise mostly from a personal need, and in the development of activities, generate resources from the sale of licenses or products. The target audience is focused on Class C, D and E and their most urgent needs are business expansion and increased sales. The main requirements for receiving investment are considered the traditional ones, for example, the type of business model, balance sheet data, positive analysis of viability and sustainability. The steps for capturing were compiled in seven steps, ranging from knowledge of the impact sector to providing feedback on the entire process. Promotion documents are the sources responsible for the greatest supply of resources. As for the challenges, professionalization of the sector and the business were the most cited. As limitations, in the quantitative part, the sample size stands out and in the qualitative stage, the difficulty in getting contact and collaboration from social entrepreneurs is highlighted, as well as the fact that it is a study of multiple cases. Thus, for future studies, it is suggested: to reapply this research seeking to expand both the qualitative and quantitative stages in order to be able to carry out a comparative study with more information; conduct research that interconnects the ideas and information provided by impact investors and social entrepreneurs, in order to find a connection between the interest of the investor and the need of the entrepreneur; and as there are still few studies that address the issue of impact investing, it is suggested that the theme be further explored and that this be done not only in the context of administration, but also in other areas, lines of research, in such a way that it is possible in addition to expanding, making interconnections between areas that can enrich this theme.